Mapping the Culinary Lexicon: A Semantic Analysis of Dagbani Cook Verbs - Bashiru, Nurideen; Yussif, Ben Kudus (Universitas Galuh, 2025)
This study analyzes the semantic field of culinary expressions in Dagbani, a language within the Mabia group spoken predominantly in Northern Ghana. Using Cruse’s (1990) Lexical Semantics Relation Theory as a theoretical framework, the research focuses specifically on the semantics of cook-related verbs. The study adopts a qualitative research approach by identifying and examining sixteen distinct cooking verbs in Dagbani. The findings reveal that each verb tends to collocate with specific food items, and that the choice of verb is influenced by factors such as the method of preparation, the intensity of heat applied, and the presence or absence of a heat source. This analysis contributes to a deeper understanding of the relationship between language, culture, and culinary practices in Dagbani.